2003
DOI: 10.1159/000074943
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Passage of Pterygopalatine Ganglion Efferents to Paranasal Sinuses and Nasal Mucosa in Man

Abstract: Parasympathetic nerves of pterygopalatine ganglion origin are considered to enter the orbit and distribute to the nasal mucosa with the anterior ethmoidal nerve. As their distribution has never been demonstrated the present study was undertaken to seek evidence of their passage and to identify their relationship with the ethmoidal nerves. The soft tissues of the pterygopalatine fossa and orbit from sixteen sides of twelve cadavers were removed in one piece and either dissected or cut coronally into slabs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…In addition, numerous postganglionic parasympathetic branches have been shown to course superior medially from the SPG into the orbital cavity, providing parasympathetic innervations to the meningeal and cerebral blood vessels (see Fig. A and B) …”
Section: Introductionmentioning
confidence: 80%
“…In addition, numerous postganglionic parasympathetic branches have been shown to course superior medially from the SPG into the orbital cavity, providing parasympathetic innervations to the meningeal and cerebral blood vessels (see Fig. A and B) …”
Section: Introductionmentioning
confidence: 80%
“…The ramus originating from the pterygopalatine ganglion (PPG) is found to specifically innervate the nasal mucosa and it has been called the posterior nasal nerve. Selective resection of this posterior nasal nerve abolishes parasympathetic supply to the nasal cavity and provides the same benefits of vidian neurectomy, without having any of its complications 18,19 . Ikeda et al 20 observed that posterior nasal neurectomy causes suppression of the secretagogue motor and inhibition of the neurogenic inflammation induced by the parasympathetic and sensory denervation.…”
Section: Discussionmentioning
confidence: 96%
“…The orbit receives parasympathetic eff e rents from the E d i n g e r-Westphal and from the superior salivary nuclei. The inferior salivary nucleus sends fibers to the parotid gland 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The inferior division gives rise to the inferior oblique nerve, which c a rries the general visceral motor fibers (parasympathetic) to the ciliary ganglion. Short ciliary nerves, from the ganglion, innervate the ciliary body, sphincter pupillae and uveal tract glands 27,28 .…”
Section: Discussionmentioning
confidence: 99%